Pemaknaan Pesan Dalam Perilaku Celebrity Worship Fandom Carat Di Aplikasi Weverse - Hasiana, Razahra Rugunnita; Zein, Duddy; Gemiharto, Ilham (Telangke:Jurnal Telangke Ilmu Komunikasi, 2024)
This research aims to analyze the interpretation of interaction messages in Carat's celebrity worship behavior towards Seventeen on the Weverse application. The research method employed is qualitative with a phenomenological approach. Data was collected through in-depth interviews with Carat users on Weverse in Indonesia, direct observation on the Weverse application, and consultations with experts for data validity. The results of the study indicate that Carat interprets Seventeen's messages based on their expectations or happiness, creating a sense of closeness or a relationship beyond being mere fans and their idols. These findings align with symbolic interaction theory and reflect an intense-personal level in celebrity worship behavior.